Analisis Konstruksi Butir Soal Pilihan Ganda Berdasarkan Kaidah Penulisan yang Baik - Yentro K. Djo; Maya Novita Mbura (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Assessment plays a crucial role in education as it serves as a tool for measuring students’ achievement of learning competencies. One of the most widely used assessment instruments is the multiple-choice test. Despite its advantages in terms of objectivity, efficiency, and ease of scoring, the quality of multiple-choice tests largely depends on the accuracy of item construction. Previous studies have identified several common weaknesses in item development, including unclear stems, ambiguous wording, ineffective distractors, and misalignment between learning objectives and assessment indicators. Such weaknesses may reduce the validity and reliability of assessment results. This article aims to analyze the construction of multiple-choice items based on established item-writing guidelines and examine their relationship with educational quality. The study employs a literature review approach by analyzing scholarly articles, educational reports, and policy documents published between 2020 and 2025. The findings indicate that well-constructed multiple-choice items contribute significantly to the accurate measurement of learning outcomes, the development of higher-order thinking skills, and overall educational quality. In the context of East Nusa Tenggara (NTT), challenges in assessment quality are closely associated with limited teacher training opportunities and restricted access to educational resources. Therefore, strengthening teachers’ assessment competencies is a strategic priority for improving educational outcomes.